2001
DOI: 10.1074/jbc.m104279200
|View full text |Cite
|
Sign up to set email alerts
|

ActA from Listeria monocytogenes Can Interact with Up to Four Ena/VASP Homology 1 Domains Simultaneously

Abstract: The facultative intracellular human pathogenic bacterium Listeria monocytogenes actively recruits host actin to its surface to achieve motility within infected cells. The bacterial surface protein ActA is solely responsible for this process by mimicking fundamental steps of host cell actin dynamics. ActA, a modular protein, contains an N-terminal actin nucleation site and a central proline-rich motif of the 4-fold repeated consensus sequence FPPPP (FP 4 ). This motif is specifically recognized by members of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 49 publications
(43 reference statements)
2
23
0
Order By: Relevance
“…Much of what we know about the effectors of VASP in motile processes has come from the Listeria system. The N-terminal EVH1 domain of VASP binds four FPPPP proline-rich repeats on ActA (4,5,26,28,32,42,43). In eukaryotic cells, VASP is thought to regulate filament branching by some unidentified cellular machinery using the Arp2/3 complex, since filaments at the leading edge are less densely branched in the presence of VASP than in its absence (3).…”
Section: Sh2-b␤ (Src Homology 2 B␤)mentioning
confidence: 99%
“…Much of what we know about the effectors of VASP in motile processes has come from the Listeria system. The N-terminal EVH1 domain of VASP binds four FPPPP proline-rich repeats on ActA (4,5,26,28,32,42,43). In eukaryotic cells, VASP is thought to regulate filament branching by some unidentified cellular machinery using the Arp2/3 complex, since filaments at the leading edge are less densely branched in the presence of VASP than in its absence (3).…”
Section: Sh2-b␤ (Src Homology 2 B␤)mentioning
confidence: 99%
“…Wavelength scans from 190 to 260 nanometers were collected sequentially at 4,20,37,65,90,65,37,20, and ActAs using a 1-nm bandwidth and 1-nm step size. For melts at 222 nm, the temperature was increased in 5°steps with a 4.5-min equilibration time between steps.…”
Section: ϫ9mentioning
confidence: 99%
“…Analytical ultracentrifugation has demonstrated that ActA exists as a monomer in solution (20,32) with ambiguous results regarding higher order multimers (32). ActA has been shown to behave as an anomalously large species by gel filtration, suggesting that it may be an elongated molecule (32,34).…”
mentioning
confidence: 99%
“…The G-actin-binding site is not required for intracellular bacterial motility, although it plays a role in the Arp2/3-mediated actin filament nucleation in vitro (Pistor et al, 2000;Skoble et al, 2000Skoble et al, , 2001. The central proline-rich domain, which includes three to four copies of the E/DFPPPPXD/E motif (Pistor et al, 1995;Smith et al, 1996;Niebuhr et al, 1997), binds to proteins of the Ena/VASP family (Pistor et al, 1995;Smith et al, 1996;Niebuhr et al, 1997;Machner et al, 2001), which includes the mammalian proteins vasodilator-stimulated phosphoprotein (VASP), mammalian Enabled (Mena), Ena-VASP-like (EVL), and the Drosophila protein Ena (Gertler et al, 1990(Gertler et al, , 1996Halbrugge et al, 1990).…”
Section: Introductionmentioning
confidence: 99%